Enhancing DSSC conversion efficiency by ozone-treated TiO2 photoanode and optimum CNT/PDDA counter electrode - Yoshiki Kurokawa; Dang Trang Nguyen; Ryota Fujimoto; Kozo Taguchi (Institute of Advanced Engineering and Science, 2020)
The conversion efficiency of dye-sensitized solar cells (DSSCs) depends on the performance of the photoanode and the counter electrode. In this paper, UV-ozone treatment has been applied to the photoanode to clean and increase the hydrophilicity of the photoanode. As a result, the dye adsorption capacity was improved. Also, low-cost multiwalled carbon nanotube (CNT) combined with poly (diallyl dimethylammonium chloride) (PDDA) was used to fabricate the counter electrode. The CNT/PDDA counter electrode was optimized to maximize its performance. By using the ozone-treated photoanode and optimum CNT/PDDA counter electrode, the conversion efficiency has increased by about 64%.